Inventory of butterfly species in Kali Pethuk, Rahtawu Village, Gebog District, Kudus Regency - Martitik, Dwiyani Anjar; Regita, Puteri; Uzla, Early Deswita; Yulianto, Nur (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
Indonesia is recognized for its exceptionally high biodiversity, including diverse insect groups such as butterflies, which act as pollinators and bioindicators of ecosystem health due to their sensitivity to habitat changes. This study aimed to inventory butterfly species in the Kali Pethuk area, Kudus Regency, Central Java, using a field observation method with an exploratory survey approach. Observations were conducted directly along the riverbanks and surrounding vegetation in May, with each session lasting 2–4 hours, employing random sampling. Eight butterfly species from four families: Pieridae, Lycaenidae, Nymphalidae, and Papilionidae were recorded. The diversity index (H') was 1.65, classified as moderate, indicating a reasonably varied butterfly community, while Eurema sp. was the most dominant species and the evenness index (E = 0.86) suggested a fairly balanced distribution among species. Data collected included the number of individuals, species richness, and abundance. These findings provide valuable baseline information for understanding local biodiversity, supporting environmental monitoring and conservation planning in riparian ecosystems, and offering a reference for future ecological studies aimed at assessing long-term changes in species composition due to anthropogenic or climatic influences.